2016
DOI: 10.4236/jsea.2016.95012
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Usage of Computer and Internet among Medical Faculties’ Students at the University of Jordan

Abstract: The rapid development of information communication technology blazed a trail in our learning, work, and lives. This study was conducted to ascertain the computer and internet literacy level of medical faculties' students. 171 first-year medical students from 4 different medical colleges of the University of Jordan participated in the study. A semi-structured questionnaire was used to collect the data and the data analysis was done by using SPSS, Version 17. The results indicated that most medical students have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The findings of the present study showed that most of the participants used the Google search engine, which is in line with Saeidi et al, (11) Scott et al, (16) and Maleki et al (17) User friendly interface and variety of capabilities of the Google search engine makes it the first choice for most internet users to search for information on the internet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study showed that most of the participants used the Google search engine, which is in line with Saeidi et al, (11) Scott et al, (16) and Maleki et al (17) User friendly interface and variety of capabilities of the Google search engine makes it the first choice for most internet users to search for information on the internet.…”
Section: Discussionsupporting
confidence: 91%
“…Saeidi et al, ( 11 ) argued that these findings indicate high level of access to computers and the internet in societies and that level of access to online information was a necessity of modern life, especially for students. The findings of the present study showed that most of the participants used the Google search engine, which is in line with Saeidi et al, ( 11 ) Scott et al .,( 16 ) and Maleki et al ( 17 ) User friendly interface and variety of capabilities of the Google search engine makes it the first choice for most internet users to search for information on the internet.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study showed the same results when conducted among 171 first-year medical students at the University of Jordan, indicating that most students had an average or somewhat advanced knowledge of using the computer and internet. 11 Furthermore, the same study found that lack of time, connectivity issues, and resources are still a constraint. Another study was done at the University of Edinburgh, in which 144 3rd year students were assessed for the levels of computing skills and confidence for carrying out tasks.…”
Section: Discussionmentioning
confidence: 98%
“…[4,[8][9][10] Test-retest reliability was estimated with 15 students by taking two interviews seven days apart, and this was not included in the final analysis. Internal consistency reliability by Cronbach's alpha coefficient was 0.83.…”
Section: Methodsmentioning
confidence: 99%